Improvement of Potato-Jute -T. Aman Cropping Pattern Through Inclusion of Mungbean - Chowdhury, AK; Zahan, T; Anowar, MM; Islam, MK; Molla, SH; Khan, ASMM Rahman (Bangladesh Agronomy Journal, 2018)
Inclusion of mungbean in a cropping pattern not only increases the cropping intensity but also enriches soil health as well as ensures nutrition for the fast-growing population of Bangladesh. A study was conducted in farmers’ field of Domar, Nilphamari, Bangladesh during 2013-14 and 2014-15 to evaluate the performance of four-crop based cropping pattern Potato – Mungbean – Jute - T.Aman rice against the existing farmer’s pattern Potato-Jute-T.Aman rice. The experiment was laid out in randomized complete block design with six disperse replications. Two-year study revealed that inclusion of mungbean and practice of better management along with use of modern high yielding varieties in the existing cropping pattern increased rice equivalent yield of the whole pattern by 38.7% and economic profit by 73.1%. Moreover, land use efficiency and production efficiency of Potato – Mungbean – Jute -T.Aman pattern were higher than the existing pattern by 14.0 and 28.2%, respectively. Thus, the study suggests incorporation of mungbean in the existing Potato-Jute-T.Aman pattern could be a agronomically and economically profitable for the farmers as well as cropping intensity can be increased. Bangladesh Agron. J. 2017, 20(2): 87-95